2023
DOI: 10.3390/pharmaceutics15020667
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Inhaled Ethanol in Early-Stage SARS-CoV-2 Infection in Older Adults: A Phase II Randomized Clinical Trial

Abstract: Background: Inhaled ethanol in the early stages of SARS-CoV-2 infection may reduce the viral load, decreasing progression and improving prognosis. The ALCOVID-19 trial was designed to study the efficacy and safety of inhaled ethanol in older adults at initial phases of infection. Methods: Randomized, triple-blind, placebo-controlled phase II clinical trial. Experimental group (n = 38) inhaled 65° ethanol through an oxygen flow, while in the control group (n = 37), water for injection was used. General endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Notably, neither the treated animals nor the controls' histology samples showed any signs of damage. A recent randomized controlled trial (RCT) from the same group has confirmed these data in humans [ 12 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Notably, neither the treated animals nor the controls' histology samples showed any signs of damage. A recent randomized controlled trial (RCT) from the same group has confirmed these data in humans [ 12 ].…”
Section: Discussionmentioning
confidence: 95%
“…Now, if this might have been acceptable in 2020, at present, the evidence showed by Pro et al [ 8 ] should lead to a selective update, at least. Particularly, the RCT from the Spanish group [ 12 ] found a faster and higher - even not significative - reduction of the viral load in the EtOH-treated patient's group versus controls. Unfortunately, the RCT had to be ended earlier for insufficient recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol poisoning [11], fat embolism [12], premature labor prevention [13], preeclampsia [14], and pulmonary edema [15] have all been treated with ethanol-specific treatments in the past. Castro-Balado et al [16] have shown the histological safety of inhalation ethanol treatment on rats' lungs and respiratory systems. Ethanol was authorized by the Food and Drug Administration.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of concern has been expressed regarding the potential mucosal harm that breathed ethanol might cause. Castro-Balado et al careful research[16] appears to have completely dispelled these concerns. It should be noted that spraying into the mask prolongs the action of the nebulized liquid and maintains its efficiency by reducing the dispersion and evaporation of the liquid.…”
mentioning
confidence: 99%